2014
DOI: 10.1111/bju.12603
|View full text |Cite
|
Sign up to set email alerts
|

Role of urinary cations in the aetiology of bladder symptoms and interstitial cystitis

Abstract: ObjectivesTo identify and characterise urinary cationic metabolites, defined as toxic factors, in patients with interstitial cystitis (IC) and in control subjects. To evaluate the cytotoxicity of the urinary cationic metabolite fraction of patients with IC vs control subjects and of individual metabolites in cultured urothelial cells. Subjects and MethodsCationic fractions (CFs) were isolated from the urine specimens of 62 patients with IC and 33 control subjects by solid-phase extraction. CF metabolites were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…In this model, no overt damage is produced with ChABC and only a mild inflammation and edema is induced by dilute PS. Numerous other studies in the past have indicated that treatments such as HCl (8) or PS (20,30) can increase permeability of the bladder, and others have shown that IC patients have more permeable bladders (2,20,22,24). The role of the GAG layer was inferred.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In this model, no overt damage is produced with ChABC and only a mild inflammation and edema is induced by dilute PS. Numerous other studies in the past have indicated that treatments such as HCl (8) or PS (20,30) can increase permeability of the bladder, and others have shown that IC patients have more permeable bladders (2,20,22,24). The role of the GAG layer was inferred.…”
Section: Discussionmentioning
confidence: 94%
“…Typically, only a relatively lowgrade inflammation with some mast cells and neutrophils is present (9,17,31) and a mild inflammatory gene expression profile is seen in IC patients (16), although severe inflammation can sometimes be seen in patients with Hunner's lesion (17). Interestingly, there is credible evidence that excess organic polycations such as protamine or smaller molecules in urine (24,28) or the loss of polyanionic glycosylation of Tamm-Horsfal protein (23) (loss of scavenger function) can damage the GAG layer and, if chronic, could lead to a loss of urothelial terminal differentiation and appearance of symptoms due to chronic increased permeability. Thus the models presented here could be representative of a natural disease process if made chronic.…”
Section: Discussionmentioning
confidence: 99%
“…Parsons et al. suggested that cationic urinary components could potentially be cytotoxic to the urothelial cells, resulting in bladder mucosal injury 52,53 . Some dietary metabolites, medications and nutritional supplements also exert cytotoxic effects on the urothelium 26 .…”
Section: Pathophysiology Of Ic/bpsmentioning
confidence: 99%
“…18,19 Recent studies in male and female IC patients reported that patients have more than a twofold increase in urinary cationic organic metabolites, compared with control participants, that are toxic to cultured urothelial cells. 20,21 It is proposed that these cations injure the bladder mucus barrier, and initiate the IC cascade of epithelial leak and potassium diffusion into the bladder wall. These reports were from one center, UCSD.…”
Section: Introductionmentioning
confidence: 99%